Is the use of the coefficient of variation a valid way to assess the swimming intra-cycle velocity fluctuation? - Gonjo, T.; Fernandes, R. J.; Vilas-Boas, J. P., Sanders, R. (Journal of Science and Medicine in Sport, 2023)
Objectives Swimming intra-cycle velocity fluctuation has often been assessed using the coefficient of variation, which requires a mathematical assumption of a positive linear relationship between the velocity mean and standard deviation. As this assumption has never been tested, the current study aimed to investigate the within-participant relationship between the mean and standard deviation of the intra-cycle velocity.